Adölesanlarda sağlıklı seçi̇mler programı'nın beslenme, fi̇zi̇ksel akti̇vi̇te ve vücut ki̇tle indeksi̇ne etki̇si̇ - Duygu Özmet, Tuğba (My University, 2023)
Amaç: Bu çalışma “Sağlıklı Seçimler nın adölesanlarda etkinliğini değerlendirmek amacıyla yapıldı. Gereç ve Yöntem: Çalışmamızda ön test son test kontrol gruplu yarı deneysel tasarım kullanıldı. Bu çalışma Mayıs 2022-Ocak 2023 tarihleri arasında gerçekleştirildi. İstanbul’da bulunan iki ortaokuldaki 5.,6.,7.sınıfta okuyan 150 adölesan çalışmaya dahil edildi. Okullardan biri girişim (n=75), diğeri kontrol grubu olarak (n=75) belirlendi. Girişim grubuna altı oturumluk eğitim verildi. Veriler Tanıtıcı Özellikler Formu, Sağlıklı Alışkanlıklar Anketi, Adölesan Tutum Ölçeği, Adölesan Fiziksel Aktivite Bilgi Ölçeği, Adölesan Beslenme Bilgi Ölçeği ve Fiziksel Aktivite Anketi kullanılarak toplandı. Verilerin analizinde ki-kare testi, t testi, Mann-Whitney U testi ve Wilcoxon testi kullanıldı. Bulgular: Çalışmamızda program sonrası girişim grubunda günlük kahvaltı sayısı, fiziksel aktivite süresinde artış gözlendi. Son test ve izlem döneminde girişim grubunda gazlı içecek, hazır kutu meyve suyu tüketimi yönünden azalma; su ve süt tüketimi yönünden artış saptandı. Ayrıca son test ve izlem dönemlerinde ön teste göre vücut kitle indeksinde azalma bulundu. Fazla kilolu ve obez adölesanlarda girişim grubunda son test beslenme bilgi puan ortancası, izlem aktivite bilgi puanı, son test tutum ortancası, son test fiziksel aktivite puan ortancası kontrol grubuna yüksekti. Sonuç: Bu sonuçlar Sağlıklı Seçimler nın sağlıklı beslenme ve fiziksel aktivite alışkanlıklarını kazandırmada etkili olduğunu gösterdi.

Objective: This study was conducted to evaluate the effectiveness of the Healthy Choices Program on adolescents. Materials and Methods: In our study, a quasi-experimental design with a pre-test and post-test control group was used. This study was carried out between May 2022 and January 2023. 150 adolescents in the 5th, 6th and 7th grades of two secondary schools in Istanbul were included in the study. One of the schools was designated as the intervention group (n=75) and the other as the control group (n=75). Six sessions of training were given to the intervention group. Data were collected using the Descriptive Characteristics Form, Healthy Habits Questionnaire, Adolescent Attitude Scale, Adolescent Physical Activity Knowledge Scale, Adolescent Nutrition Knowledge Scale and Physical Activity Questionnaire. Chi-square test, t test, Mann-Whitney U test, Wilcoxon test were used to analyze the data. Results: In our study, an increase in the number of daily breakfasts and physical activity duration was observed in the intervention group after the program. Between the last test and follow-up period, there was a decrease in the consumption of carbonated drinks and ready-made fruit juice in the intervention group; An increase was detected in water and milk consumption. Additionally, a decrease in body mass index was found in the posttest and follow-up periods compared to the pretest. In overweight and obese adolescents, the median post-test nutrition knowledge score, follow-up activity knowledge score, post-test attitude median, and post-test physical activity score median in the intervention group in overweight and obese adolescents were higher than the control group. Conclusion: These results showed that the Healthy Choices Program was effective in gaining healthy eating and physical activity habits.
Effect of healthy choices program on nutrition, physical activity and body mass index in adolescents
Keywords: Adolesan; Adolescence; Adölesan; beslenme; fiziksel aktivite; Gençlik; healthy choices; nutrition; okul sağlığı; physical activity; sağlıklı seçimler; school health; Social conditions; Sosyal durum; Turkey; Türkiye; Youth